A Nationwide Population-Based Retrospective Cohort Study of the Risk of Uterine, Ovarian and Breast Cancer in Women With Polycystic Ovary Syndrome. (19th November 2014) - Shen, Cheng-Che; Yang, Albert C.; Hung, Jeng-Hsiu; Hu, Li-Yu; Tsai, Shih-Jen
Abstract: Background: Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders among women of reproductive age. We used a nationwide population-based retrospective cohort study to explore the relationship between PCOS and the subsequent development of gynecological cancers including uterine, breast, or ovarian cancer. Methods: We identified subjects who were diagnosed with PCOS between January 1, 2000, and December 31, 2004, in the Taiwan National Health Insurance (NHI) Research Database. A comparison cohort was constructed for patients without known PCOS who were also matched according to age. All PCOS and control patients were observed until diagnosed with breast cancer, ovarian cancer, or uterine cancer or until death, withdrawal from the NHI system, or December 31, 2009. Results: The PCOS cohort consisted of 3, 566 patients, and the comparison cohort consisted of 14, 264 matched control patients without PCOS. The adjusted hazard ratio (HR) of uterine cancer and breast cancer in subjects with PCOS were higher (HR: 8.42 [95% confidence interval: 1.62–43.89] and HR: 1.99 [95% confidence interval: 1.05–3.77], respectively) than that of the controls during the follow-up. With the Monte Carlo method, only the mean adjusted HR of 1, 000 comparisons for developing uterine cancer during the follow-up period was greater for the PCOS group than for the control groups (HR: 4.71, 95% confidence interval: 1.57–14.11). Conclusion: PCOS might increase the risk of subsequent newly diagnosed uterine cancer. It is critical that further large-scale, well-designed studies be conducted to confirm the association between PCOS and gynecological cancer risk. Abstract : This study used a nationwide population-based retrospective cohort study to explore the relationship between polycystic ovary syndrome (PCOS) and the subsequent development of gynecological cancers including uterine, breast, or ovarian cancer. The results indicate that PCOS might increase the risk of subsequent newly diagnosed uterine cancer, but it is critical that further studies be conducted to confirm the association between PCOS and gynecological cancer risk.